Conceptual change in secondary chemistry : the role of multiple analogical models of atoms and molecules. - Harrison, Allan G. (Curtin University, 1996)
Chemistry textbooks and teachers frequently use a variety of metaphors, analogies and models to describe atomic and molecular structures and processes. While it is widely believed that multiple analogical models encourage students to construct appropriate mental models of chemical phenomena, uncritical use of multiple analogical models may actually be responsible for a number of alternative conceptions in chemistry. Students hear and read about electron clouds and shells, atoms that are like miniature solar systems and balls, and molecules that are simultaneously represented by balls-and-sticks, joined spheres, electron-dot and structural diagrams. A strong case has been made that students try to integrate these diverse analogical models resulting in the generation of unscientific synthetic models. Conceptual change research programs also propose that carefully designed teaching and learning activities can stimulate students to exchange their intuitive and synthetic conceptions for more scientific conceptions.This thesis investigates the occurrence of students' intuitive and synthetic mental models of atoms and molecules at both a general and specific level. The investigations consisted in the first phase of semi-structured interviews with 48 Year 8-10 science students. While the data were predominantly qualitative the interviews also generated simple quantitative data. The second phase was wholly qualitative and involved the researcher as teacher' in the Year 11 class. Portfolios were compiled for each student in the class and six portfolios were interpreted to produce a set of case studies describing the students' learning about atoms, molecules and bonds. These data were derived from transcripts of class discussions and individual interviews; pre-tests, formative tests and post-tests; student essays and worksheets and analogical teaching events. The data were interpreted from a constructivist viewpoint with attention given to credibility, viability and transferability, and dependability. The desire to collect every piece of useful data was constrained by the ethical need to minimise the disruptive effect of the research on the students' normal learning.The first or general phase of this study investigated the question: With what models of atoms and molecules are lower secondary science students familiar? The interviews about atomic and molecular conceptions held by the Year 8-10 students found, for example, that some students confused atoms with cells because both have a nucleus, while others believed that electron shells enclose and protect the atom. All but two students visualised atoms with large nuclei and close static electrons. A majority of this student sample were confused by ball-and- stick molecular models and had a strong preference for space-filling molecular models because they were more 'real'.The second or specific phase of this study consisted of an in-depth study of the development of mental models of atoms, molecules and bonds by six Year 11 chemistry students over 40 weeks of instruction. This study investigated the question: Do systematically presented multiple analogical models help students change their conceptions of atoms, molecules and bonds in favour of the scientific view? The students' prior mental models of an atom were dominated by a solar system model with the electrons in simple shells. A variety of metaphors, analogical models and explanations emphasising the diffuse spaciousness of atoms helped three students restructure their conceptions in favour of the scientific concept. Students also were encouraged to identify the shared and unshared attributes of familiar molecular models and, in time, three students became competent multiple modellers. It is claimed that these three students changed their conceptions of atoms and molecules in the sense that they realised that models are thinking and communicative tools, not reality itself. The significant change in these students' thinking was their recognition that atomic and molecular analogical models are context-dependent.The phase two study's pre-occupation with conceptual change or knowledge restructuring raised an important methodological question: Is a multi-dimensional approach a better way to interpret conceptual change learning? or, are the various theoretical perspectives on conceptual change complementary? The study's theoretical framework found that conceptual change learning can be interpreted from epistemological, ontological, motivational, holistic explanatory and developmental perspectives. The collection and analysis of the data showed that student modelling ability and Perry's model of intellectual development were powerful interpretive tools when data needed to be examined from multiple perspectives. The six case studies support the assertion that multi-dimensional interpretive frameworks have superior credibility and viability compared to uni-dimensional studies.Finally, the research raised several questions requiring further investigation. No direct support was found for the claim that dissatisfaction is central to conceptual change. This issue needs much more study due to the popularity of discrepant event teaching. While a multi-dimensional conceptual change model has been synthesised, this model needs further refinement as does the issue of how to monitor the status of students' conceptions. A most promising line of pedagogical research is the value of teaching scientific modelling through the use of multiple systematic analogical models.